Failure of iron to promote attachment of gonococci to human spermatozoa under physiological conditions. Issue 5 (October 1979) - Johnson, A P; Osborn, M F
Abstract : The effect of iron on the attachment of gonococci to human spermatozoa was investigated using the three iron salts, ferric chloride, ferric nitrate, and ammonium ferric citrate (AFC). Ferric chloride and ferric nitrate were found to be unsuitable for such studies because they were insoluble at physiological pH values, produced a marked decrease in the pH of unbuffered medium (Ringer's solution), and agglutinated spermatozoa. AFC, in contrast, was soluble at physiological pH, did not affect the pH value of Ringer's solution, and did not agglunate spermatozoa. When gonococci and spermatozoa were mixed together in media with and without AFC, the proportion of spermatozoa with adherent gonococci was approximately the same in each case. Thus, in contrast to previous report, we have found that the addition of iron does not increase the attachment of gonococci to human spermatozoa.